PENGARUH SALEP EKSTRAK DAUN BINAHONG (Anredera cordifolia) FRAKSI ETANOL TERHADAP KESEMBUHAN LUKA IRIS SECARA FISIK PADA ANJING (Canis familiaris) - , FAJAR KURNIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Dog (Canis familiaris) was one of pet potentially get injuries or wounds. Binahong (Anredera cordifolia) was one of herbs widely used for curing wounds. The objective of this research was to study the effect of binahong leaves extract ointment ethanol fraction 5% and 10% toward incision wound healing in dogs physically. Four domestic female healthy dogs were used in this research. The dogs were adapted for one week and given anthelmintic. Three incision throughout Â± 6 cm were done (Group A, B and C) on each dog at the left side of the abdomen by vertical fashion. A mashed fresh binahong leaves, binahong leaf extract ointment 5% ethanol fraction, and binahong leaf extract ointment 10% ethanol fraction were treated to incision wound of group A, B, and C respectively. The dayly observation on the wound healing progress done visually with parameter of swelling, redness, wetness, and the link between the two wound's for seven days. Observation results shows that in group A, the swelling and redness was not evident, the wound also dried and closed in the third day. In group B swelling is not evident on fifth day, redness was not evident, dried and closed in the fourth day. Mean while in group C the swelling and redness was not evident, the wound also dried and closed in the fourth day. Based on the results research and discussion, it could be concluded that the binahong leaves extract ointment ethanol fraction concentration 10% giving better results than the binahong leaves extract ointment ethanol fraction concentration of 5% in forming a primary healing, but not better than the control (mashed fresh binahong leaves). Further research needs to be conducted for getting the best formula of binahong leaves extract ointment for skin wound therapy.